Antimicrobial and Other Pharmacological Properties of Ocimum basilicum, Lamiaceae - Kairat Zhakipbekov; Aknur Turgumbayeva; Sholpan Akhelova; Kymbat Bekmuratova; Olga Blinova; Gulnara Utegenova; Klara Shertaeva; Nurlan Sadykov; Kuanysh Tastambek; Akzharkyn Saginbazarova; Kenzhebek Urazgaliyev; Gulbanu Tulegenova; et al. (Molecules, 2024)
Since ancient times, various scientists and doctors have utilized different herbs to heal diseases. Due to the rise in drug resistance and the negative effects of chemosynthetic drugs, researchers and the general public around the world have become more interested in medicinal herbs and plant metabolites/extracts. This is due to its non-toxicity and its several health benefits when used to treat diseases in clinical and medical settings. Ocimum basilicum is one such plant, possessing a wide range of bioactive phytochemicals including alkaloids, phenolics, flavonoids, tannins, saponins, reducing sugars, cardiac glycosides, steroids and glycosides, as well as complex pharmacological activities, including anti-inflammatory, antifungal, antibacterial, antioxidant, wound healing and antiviral properties. The results of many studies on Ocimum basilicum plant extracts are collected and presented in this review. The plant extracts have excellent potential to be used as medicinal raw materials, and exhibit an extensive variety of therapeutic capacities, including antibacterial, antioxidant, wound healing, anti-inflammatory, antifungal, and antiviral properties.